University Students’ Challenges In The Implementation Of Project-Based Learning - Adinda Apriliani Hardono; Fenny Yutika Seli (South Sulawesi Education Development (SSED), 2025)
Project-Based Learning (PBL) is a key pedagogical approach in higher education, particularly in English Education programs, fostering critical thinking and collaboration. However, students face challenges such as time management, lack of motivation, limited resources, and peer collaboration difficulties. This study used mixed methods, including questionnaires and interviews with English Education students in Jakarta, to explore these issues. Findings indicate a need for clearer project guidelines, enhanced instructor support, and better access to technology. The study highlights the importance of targeted support mechanisms to improve PBL effectiveness. Institutions should prioritize collaboration, structured guidance, and resource availability to help students maximize the benefits of PBL in developing 21st-century skills. The study has several limitations. It focuses only on university students in Jakarta studying English Education, limiting the generalizability of the findings. While questionnaires are efficient, they may yield brief responses, and interviews, though insightful, involve fewer participants.